2023
DOI: 10.56778/jdlde.v1i8.76
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Online Learning VS Face-To-Face Learning on Student Learning Motivation Post the Covid - 19 Pandemic at Schools and Colleges

Abstract: This study aims to look at a comparative description of learning motivation during online learning and face-to-face learning after the end of the Covid pandemic. The Covid-19 disease outbreak is a situation beyond predictions that has brought urgent changes in various sectors of activity including in the world of education. The development of the virus quickly spread throughout the world. This affects policies to be implemented in the world of education by changing learning that has to come to class to be suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…5. Errors in Drawing Conclusions (Re-proving or Drawing Conclusions) This error occurs because students do not know or do not understand the procedure for solving mathematics story problems correctly, so students understand that after finding the answer, then the solution is complete and the conclusion is not correct (Liefgreen & Lagnado, 2023); (Abidin et al, 2023) important to do. The following is an excerpt from an interview conducted with ST.…”
Section: Resultsmentioning
confidence: 99%
“…5. Errors in Drawing Conclusions (Re-proving or Drawing Conclusions) This error occurs because students do not know or do not understand the procedure for solving mathematics story problems correctly, so students understand that after finding the answer, then the solution is complete and the conclusion is not correct (Liefgreen & Lagnado, 2023); (Abidin et al, 2023) important to do. The following is an excerpt from an interview conducted with ST.…”
Section: Resultsmentioning
confidence: 99%
“…In a study (Abidin, Hasibuan, & Harahap, 2023), it was found that face-to-face meetings made people more interested in learning. The interaction activities carried out during the implementation of the learning process-both direct interactions with peers and interactions with subject teachers-have an impact on this.…”
Section: Methods Of Islamic Religion Teachers In Improving Post-onlin...mentioning
confidence: 99%
“…In this regard, learning motivation is related to the psychological aspects of each individual student, so that this will arouse students' enthusiasm to learn actively. This motivational factor must be taken into account by the teacher during the learning process, especially in Islamic religious education classes (Wahyuni & Bhattacharya, 2021) (Abidin et al, 2023). Some of the students' efforts in generating positive learning enthusiasm are generally influenced by several factors which become influential aspects of the amount of learning motivation possessed by each individual student.…”
Section: Motivation To Learnmentioning
confidence: 99%